Representasi Maskulinitas dalam Program Tayangan entertaiment News Net.TV (Studi Semiotika pada SegmenMix and Match -Tips and Trick Fashion dalam Tayangan Entertaiment NewsdiNet.TV) - Muttaqin, Luthfia Aziza, Ratri Kusumaningtyas, M.Si (2017)
Media becomes a part of society life nowadays. As the society need information and entertainment, the emergence of media printing and media electronic help them to get it as they want. People as audience who have an active manner related to media sort and choose information which is delivered by the media depends on their needs. Media becomes one of the means which takes part in masculinity image. By means of media, some parties attempt to give a masculinity description concept now. The description of masculinity is represented by the picture and the sound in television. Masculinity is a man stereotype embodied by a woman cloth, appearance, and occupation. Man gender stereotype is supposed as socio cultural demand. The research focuses on fashion tips and trickvideo specifically for man which is presented in 2015. The researcher employed qualitative method using semiotics analysis by Roland Barthes. The semiotics analysis is chosen because this research identifies the myth and the masculinity sign. The result shows that a man is aware of his apperance, well maintained and follows the fashion trend in video. Masculinity is representaed by fashion style, body treatment and the use of accecories indicating the image which want to be accentuated by each man in that video. In the video, the masculinity tends to be metrosexual, a man is directed to do consumption in achieving the ideal masculinity according to fashion expert or fashion